Pracademics in criminal justice - Turgoose, Di; Knight, Victoria; Woodward, Darren (Routledge, 2025)
"Providing an in-depth interrogation of the practitioner/academic role within the context of criminal justice, this book outlines the benefits and challenges of different roles through exploring the lived experience of the contributing authors. Arranged into three comprehensive sections, the book acknowledges the contribution pracademics make to criminal justice, conceptualises pracademia in the criminal justice context, and explores what it means to be a pracademic in a criminal justice setting. Exploring the theoretical, methodological, philosophical, practice and pedagogic value that practical application brings to teaching, learning and research, the book collectively develops a pracademic model framed within the context of criminal justice, which challenges the established 'historical/traditional' wisdom of academia with the aim of disrupting traditional knowledge production, contributing to new discussions and highlighting the value of scholarship grounded in practice in criminal justice. Written and edited by pracademics with extensive criminal justice experience, Pracademics in Criminal Justice will be of value to anyone with an interest in how practice and academia intertwine in a criminal justice setting, including pracademics, academics, practitioners, applied academics, those with lived experience of practice in academia, activists, practivists and students, particularly those undertaking professional programmes, in areas such as policing or probation, or seeking careers as practitioners in the criminal justice system"--